Hong Kong's history : state and society under colonial rule - Ngo, Tak-Wing, 1962- (Routledge studies in Asia's transformations., 1999)
Drawing together contributions from historians, sociologists and political scientists the book highlights the role played by a variety of social actors in Hong Kongs history.